PENGARUH PERAN KELUARGA DALAM PENCEGAHAN DAN PENANGANAN PERILAKU AGRESIF PREHOSPITAL PADA ORANG DENGAN KELAINAN JIWA - Wittin Khairani; Yusniarita Yusniarita (Politeknik Kesehatan Kemenkes Bengkulu, 2022)
Clients with aggressive behavior are taken by force to mental hospitals, often appear to be inhumanly bound accompanied by shouts and escorts by a number of family members.. Family is the closest person who can provide support, attention and affection to family members who behave aggressively before being taken to the hospital which can adoptive a sense of optimism and adoptive positive thoughts in dealing with a problem. Objective: To determine the influence and differences in the role of the family in the prevention and treatment of aggressive behavior pre-hospital before and after in ODGJ clients. The study used a quasi-experimental design with a pre-test and post-test nonequivalent control group design. The study population was all patients who had a psychiatric history visited the Gamping II Public Health Center Yogyakarta in January 2021, with a sample of 30 people conducted by purposive sampling. The data collection instrument used a questionnaire on Knowledge of Prevention and Handling of Prehospital Aggressive Behavior. Data were analyzed by univariate and bivariate with t-test (95% CI). There is an influence in the form of increasing the role of the family, seen from the difference in the average value from the pre-test to the posttest only 7.76 . There was a difference from the pretest to the posttest value, seen from the significant p = 0.000 (p <0.05) after being given treatment/intervention about the role of the family in the prevention and management of prehospital aggressive behavior in ODGJ clients.There is an influence and difference after the intervention to respondents regarding the role of the family in the prevention and management of aggressive prehospital behavior on ODGJ clients.